Cerium anomaly as a tracer for paleo-oceanic redox conditions: A thermodynamics-based Ce oxidation modeling approach - Cao, Cheng; Liu, Xiao-Ming; Chen, Jun (Frontiers in Earth Science, 2022)
Reconstructing redox conditions in the paleo-ocean is essential to understand the Earth’s biogeochemical evolution. Cerium (Ce) anomaly in marine sediments has been used to distinguish oxic versus anoxic depositional environments in the paleo-ocean. Previous studies suggested that dissolved oxygen is indispensable to cerium oxidation. Therefore, this reaction can be thermodynamically modeled to quantify oxygen contents in the ocean. This study presents a series of thermodynamics-based models to relate Ce anomaly to dissolved oxygen level. We then evaluated these models in two representatively settings, including an oxic ocean and ¬anoxic basin. Finally, we examined the modeled relationship on a compiled dataset of cerium anomaly and dissolved oceanic oxygen content. These models suggest that the cerium anomaly is quantitatively related to oceanic oxygen, pH, and phosphate concentration. Notably, the results suggest that cerium anomaly is not sensitive to changes in dissolved oxygen in oxic environments. By contrast, Ce anomaly is well correlated with dissolved oxygen in anoxic environments, and it was less affected by pH and phosphate concentration. This research has significant implications for using lanthanide patterns in ancient marine carbonates to quantify dissolved oxygen level, especially during anoxic events in the Paleo-ocean.